Transforming oil waste into highly conductive composites: Enabling flexible electronics through laser processing of asphaltenes; Advanced Composites and Hybrid Materials; Vol. 7 - Petrov I. S. Iljya Sergeevich; Rodriguez (Rodriges) Contreras R. D. Raul David; Frantsina E. V. Evgeniya Vladimirovna; Grinko A. A. Aleksandr Anatoljevich; Sheremet E. S. Evgeniya Sergeevna (2024, 2024)
Title screen